2011
DOI: 10.1021/la201439p
|View full text |Cite
|
Sign up to set email alerts
|

From Micelle Supramolecular Assemblies in Selective Solvents to Isoporous Membranes

Abstract: The supramolecular assembly of PS-b-P4VP copolymer micelles induced by selective solvent mixtures was used to manufacture isoporous membranes. Micelle order in solution was confirmed by cryo-scanning electron microscopy in casting solutions, leading to ordered pore morphology. When dioxane, a solvent that interacts poorly with the micelle corona, was added to the solution, polymer-polymer segment contact was preferential, increasing the intermicelle contact. Immersion in water gave rise to asymmetric porous me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
150
1
2

Year Published

2014
2014
2017
2017

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 110 publications
(157 citation statements)
references
References 25 publications
4
150
1
2
Order By: Relevance
“…Previous studies showed isoporous membranes were prepared using di-or trisolvent systems. 10,12,14 Initially, we prepared membranes using mono-and di-solvent mixtures, however, the morphologies of the PS-b-PMMA membranes did not show an ordered pore morphology ( Fig. S1 ESI †).…”
Section: Bcp Membrane Formation By Phase Inversionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies showed isoporous membranes were prepared using di-or trisolvent systems. 10,12,14 Initially, we prepared membranes using mono-and di-solvent mixtures, however, the morphologies of the PS-b-PMMA membranes did not show an ordered pore morphology ( Fig. S1 ESI †).…”
Section: Bcp Membrane Formation By Phase Inversionmentioning
confidence: 99%
“…[14][15][16] We have shown previously that this technique can be applied to produce nanoporous membranes using the amphiphilic BCPs (PS-b-PEO and PS-b-P4VP). 12.14 Several research groups also demonstrated that this method is viable to produce nanoporous asymmetric BCP membranes However, all the membranes were produced from amphiphilic block copolymers, which contain at least one hydrophobic and one or more hydrophilic segment.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…As described in the introduction, the microphase separation of block copolymers in solvent mixtures can be advantageously used for the preparation of integral asymmetric membranes by SNIPS process [42,43,46,57]. In general, the pore structure formation is tremendously influenced by a variety of parameters such as, e.g., evaporation time, solvent mixture, additives like salts, humidity, temperature, etc.…”
Section: Membrane Preparation By Self-assembly and Non-solvent-inducementioning
confidence: 99%
“…[42,43,46,57] In general, the pore structure formation is tremendously influenced by a variety of parameters such as, e.g., evaporation time, solvent mixture, additives like salts, humidity, temperature, etc. [44,[57][58][59]. Recently, the Abetz group elucidated the influence on membrane formation by using scattering methods [58].…”
Section: Membrane Preparation By Self-assembly and Non-solvent-inducementioning
confidence: 99%